The Impact Of Implementing "Let's Read" To Enhance Students' Reading Skills at SMAN 1 Kademangan Blitar - Galuh Salsabila Azara; Dian Fadhilawati (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This research explores the impact of the "Let's Read" application on enhancing the reading skills of eleventh-grade students at SMAN 1 Kademangan Blitar. Focusing on narrative texts, especially legends, the study employs a one-group pre-test post-test design to evaluate improvements in reading comprehension. Results reveal a significant increase in students' understanding and engagement with texts. The application offers an interactive, enjoyable learning experience, promoting student autonomy and critical thinking. By integrating digital tools, the study addresses limitations of traditional methods, providing insights into effective strategies for language education. This research underscores the potential of technology to transform reading practices, encouraging educators to adopt innovative approaches that cater to modern educational needs and enhance students’ overall learning experiences.